Activation pretreatment of low‐grade Ti‐slag by alkali roasting: anticaking technique and kinetics of decomposition. Issue 1 (18th September 2015) - Meng, Fancheng; Wang, Dong; Xue, Tianyan; Wang, Weijing; Liu, Yahui; Qi, Tao
Abstract: The caking of roasting products is a serious problem in the activation pretreatment of low‐grade Ti‐slag by alkali roasting, which could lead to low heat transfer efficiency and low Ti conversion. In this study, an efficient anticaking technique was developed. This technique involved low‐grade Ti‐slag desilication and anticaking additive introduction. Optimum Ti conversion conditions in alkali roasting with KMnO4 as an anticaking additive were obtained through an orthogonal test. Approximately 99% of titanium in the low‐grade Ti‐slag could be decomposed at a loosening extent of roasting products of >90% in the presence of 4 wt% KMnO4 as an anticaking additive. Kinetic study showed that an unreacted shrinking core model could be used to describe the decomposition of low‐grade Ti‐slag in alkali roasting with KMnO4 as an anticaking additive. Decomposition kinetics were characterized in two sequential stages: decomposition occurred relatively fast in the initial stage and became slower in the second stage. A mechanism of two‐stage decomposition was proposed, i.e.,  the reaction rate was controlled by a chemical reaction initially and then was controlled by inner/ash layer diffusion. Apparent activation energies were 53.6 kJ/mol in the first stage and 65.9 kJ/mol in the second stage, respectively. © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.